Metode Pembelajaran Pendidikan Agama Islam - Shalahuddin Shalahuddin; Alfina Fristiya Safitri; Rima Wira Tama; Atika Dhanasari; Siti Sakinah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic Religious Education (PAI) learning methods are strategies used by teachers to effectively convey Islamic teachings so that they are easily understood, internalized, and practiced by students. The application of appropriate methods can create a more engaging, active, and meaningful learning process, enabling students not only to acquire knowledge but also to develop Islamic attitudes and personalities. In the context of modern education, PAI learning needs to integrate a variety of approaches, ranging from lectures, discussions, demonstrations, to hands-on, experiential learning. Furthermore, learning environments such as museums, mosques, monuments, and open spaces can be utilized as resources and supporting learning media, even if these places are not specifically designed for teaching and learning activities. Utilizing these environments provides real-life experiences that help students understand Islamic values ​​contextually. Thus, PAI learning methods play a crucial role in realizing a holistic, comprehensive educational process oriented toward the formation of Islamic character.